Representation Ability through the Problem Based Learning Model (PBL) for Junior High School Students - Ajimah, Nur; Zubainur, Cut Morina; Hajidin, Hajidin (SAINTIS Publishing, 2024)
This research aims to investigate the development of mathematical representation abilities through PBL. This research approach is quantitative. The population in this study was 150 students in class VII of SMP Negeri 13 Banda Aceh, while the sample was 23 students in class VII-5. The data collec-tion technique was carried out through tests with mathematical representation ability test instru-ments which were carried out after each lesson. The data analysis technique for mathematical rep-resentation abilities is carried out by comparing students' answers to mathematical representation abilities in each lesson based on indicators of mathematical representation abilities, namely visual, symbolic and verbal. The results of the research show that students' mathematical representation abilities develop in various ways. The first indicator of mathematical representation ability is pre-senting data from a problem in the form of pictures, diagrams, graphs or tables. At the first meeting 10 out of 23 students complied, then at the second meeting 13 students met, at the third meeting 16 students complied, and the fourth meeting 20 students complied. The second indicator is solving problems involving mathematical expressions. At the first meeting 9 out of 23 students complied, then at the second meeting 12 students complied, at the third meeting 14 students complied, and at the fourth meeting 19 students complied. The third indicator is processing scientific language at the level of words, phrases and sentences. At the first meeting 12 out of 23 students fulfilled it, then at the second meeting 13 students fulfilled it, at the third meeting 15 out of 23 students fulfilled it, and at the fourth meeting 17 out of 23 students fulfilled the third indicator.